Short-term and long-term effects of a self-managed physical activity program using a pedometer for chronic respiratory disease: a randomized controlled trial - Tomioka, Shinichi; Yamada, Hidenori; Dobashi, Kunio; Fueki, Makoto; Fueki, Naoto; Kato, Daigo (Journal of Physical Therapy Science, 2017)
[Purpose] The aim of this study was to evaluate the effects of a self-managed physical activity program using a pedometer and diary on physical function, ADL, and QOL in patients with chronic respiratory disease. [Subjects and Methods] 17 outpatients with chronic respiratory disease were assessed for dyspnea, muscle strength, exercise tolerance, ADL, and QOL at baseline, after 3-, and 6-months after the start of the program. Patients were randomly assigned to “Control” or “Diary” group. In the Diary group, the number of steps was counted with a pedometer and recorded in a diary together with self-evaluation of physical activity, while patients assigned to the Control group did not use a pedometer or keep a diary. [Results] The Diary group showed significant improvement in the daily step count over time. The Diary group showed significant improvement of the dyspnea, muscle strength, and exercise tolerance at 3 months, dyspnea and muscle strength at 6 months. Significant differences found between two groups with regard to the extent of change in the muscle strength, exercise tolerance, and QOL at 3 months. [Conclusion] This study suggests that a self-managed physical activity program using a pedometer and diary can increase the level of physical activity.